Associations between intimacy in relationships and marital satisfaction across gender and in different durations of relationship - Walton Wider; Bee, Seok Chua; Jasmine Adela Mutang; Cho, Chiew Tan; Leilei Jiang; Jem Cloyd M. Tanucan; Yin Myo Thant; Lester Naces Udang (Informa UK Limited, 2025)
This study aimed to assess the associations between intimacy in relationships and marital satisfaction across genders and in five different relationship durations. A total of 1,058 participants in Malaysia were categorised at relationship durations of less than 3 years (N = 279), 3–5 years (N = 278), >5–10 years (N = 197), >10–20 years (N = 136), and >20 years (N = 168). Measures in the study covered the Personal Assessment of Intimacy in Relationships (PAI R) and the Kansas Marital Satisfaction Scale. Analyses were carried out using linear regression. The finding showed that emotional, intellectual, and recreational intimacy were the significant predictors of marital satisfaction for male and female participants. However, there was another significant predictor for the male: conventionality intimacy. In terms of relationship durations, emotional, intellectual, recreational, and sexual intimacy were the significant predictors of marital satisfaction for those in a relationship below 3 years. Recreational intimacy was an important marital satisfaction predictor across the duration of the relationship. Besides recreational intimacy, emotional intimacy was another significant marital satisfaction predictor for those in a relationship for 3–5 years and >10–20 years, and another significant predictor for those in a relationship for >5–10 years was intellectual intimacy. These observations on marital satisfaction across genders and five relationship statuses were important in our contemporary society, where the number of marriages is decreasing.